ANALYSIS OF CORROSION RATE AND REMAINING LIFE OF STEEL ON PIPELINES AT PKS PTPN 1 TANJUNG SEUMANTOH - Muhammad Zulfri; Nazaruddin Abdul Rachman; Muhammad Isra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Corrosion is a major cause of early failure in palm oil mill infrastructure in Aceh, Indonesia. Therefore, the aim of this study is to analyze the corrosion rate of steel used in the palm oil mill industry and determine the remaining life of the steel. Round bars and plates made of steel were used as exposure samples. This sample was cleaned of impurities and ground with sandpaper to obtain a 600 grating, then washed with clean water and rinsed with strong liquid, then presented to the climate at the PTPN 1 Tanjung Seumantoh palm oil mill so that it could see the rate of steel erosion due to corrosion. For exposure, steel specimens are placed on racks, and weight measurements are taken once a month to determine corrosion rate values using the ASTM G50 standard. In addition, steel thickness measurements were also carried out in 2021 and 2022 to calculate the corrosion rate using the Standard API 570 standard.Â Research results of the remaining life of the pipe on the wall tube is about 32 years. the remaining life for the generating pipe is about 29 years, and the remaining life for the heater pipe is about 11 years. from the calculation results obtained the longest remaining life is obtained on the wall pipe while the shortest remaining life of the pipe is found in the heater pipe because the pipe is always heated.